SV40 in human thyroid nodules - Ozdarendeli, A; Camci, C; Aygen, E; Kirkil, C; Toroman, ZA; Dogru, O; Doymaz, MZ (Elsevier Science Bv, 2004)
Background: Simian virus 40 (SV40) has been a model experimental system for the study of cell transformation and tumorigenesis for many years. The study of SV40 in humans has aroused interest in the related BK virus (BKV) and JC virus (JCV) and their role in human disease. Objectives: SV40 has been found in a variety of human samples, both malignant and normal. Many independent studies have suggested that SV40 plays a role for some cancers. However, in most cases the role of SV40 remains unclear. Study design: The subject of this study consisted of 99 patients with thyroid nodules. Both thyroid nodule and normal thyroid tissue were taken from each patient to test whether they contained SV40 sequences. Results: We detected SV40 sequences by polymerase chain reaction (PCR) in four of 99 thyroid nodules. Two of them were papillary thyroid carcinomas and the others were benign thyroid nodules. No SV40 was detected in 99 of normal tyhroid tissues of the same patients. DNA sequence analysis, performed in four positive samples, confirmed that PCR products belong to the SV40 T antigen (Tag) region. Conclusion: The possible role of SV40 in the development of thyroid nodules and the spread of SV40 by horizontal infection in the human population are discussed. (C) 2004 Elsevier B.V. All rights reserved.
Keywords: SV40; thyroid nodules; PCR